Persepsi Siswa MTs Nurul Khoiroh Terhadap Urgensi Pendidikan Agama Islam Sebagai Bekal dalam Kehidupan Tahun Ajaran 2024/2025 - Hirzun Navis; Putri Maja Mulia Kulzum; Feni Laventia (Jurnal Wahana Literasi Pendidikan, 2026)
This study aims to determine the perceptions of students at MTs Nurul Khoiroh regarding the importance of Islamic Religious Education (PAI) as a provision for living life, as well as to identify the factors influencing the formation of those perceptions. Islamic Religious Education plays a strategic role in shaping students’ character, morality, and spiritual values amid the challenges of globalization and the moral crisis faced by today’s youth. This research employs a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. The subjects of the study are students from various grade levels at MTs Nurul Khoiroh. The results show that, in general, students have a positive perception of Islamic Religious Education. They believe that PAI is important not only for cognitive development but also as a moral and behavioral guide for living an Islamic way of life. However, some students stated that the learning process tends to be too theoretical and lacks practical relevance to real-life situations. Factors influencing students’ perceptions include internal factors such as family background, personal spiritual experiences, and interest in religious studies. External factors include teaching methods, the religious environment at school, and the relevance of the material to students’ daily lives. This study concludes that a positive perception of PAI can be cultivated through contextual teaching approaches that engage both the emotional and social aspects of students.